2017
DOI: 10.1002/14651858.cd011244.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco packaging design for reducing tobacco use

Abstract: The available evidence suggests that standardised packaging may reduce smoking prevalence. Only one country had implemented standardised packaging at the time of this review, so evidence comes from one large observational study that provides evidence for this effect. A reduction in smoking behaviour is supported by routinely collected data by the Australian government. Data on the effects of standardised packaging on non-behavioural outcomes (e.g. appeal) are clearer and provide plausible mechanisms of effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 75 publications
12
68
0
Order By: Relevance
“…Tobacco control efforts have focused on changing the environment and the opportunities available to individuals (e.g. legislation introducing smoke-free places, warning-labels on tobacco products) [129][130][131], which coincides with the demi-regularities we have found in our review. However, for many other modifiable risk behaviours including alcohol and physical inactivity, public health promotion has traditionally relied on education, information, and psychosocial interventions to persuade individuals to adopt healthy lifestyles [132,133].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Tobacco control efforts have focused on changing the environment and the opportunities available to individuals (e.g. legislation introducing smoke-free places, warning-labels on tobacco products) [129][130][131], which coincides with the demi-regularities we have found in our review. However, for many other modifiable risk behaviours including alcohol and physical inactivity, public health promotion has traditionally relied on education, information, and psychosocial interventions to persuade individuals to adopt healthy lifestyles [132,133].…”
Section: Discussionsupporting
confidence: 69%
“…Significant strides have been made in the field of tobacco control to reduce the prevalence of smoking globally [129][130][131]. Tobacco control efforts have focused on changing the environment and the opportunities available to individuals (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The UK Department of Health estimates that standardised packaging will have a net benefit to government of £25 billion ten years post-implementation (Department of Health, 2015). It is critical that countries robustly evaluate the impacts of this measure (Vardavas et al 2017) and do so over the longer term; a major limitation identified in a Cochrane review was the absence of research exploring the longer-term impacts of standardised packaging (McNeill et al 2017). While our findings provide support for standardised packaging during the transition period, research is needed to explore the intended and any unintended consequences of this policy in the UK (and elsewhere) after it has been fully implemented.…”
Section: Discussionmentioning
confidence: 86%
“…Smoking is the biggest culprit; globally, 25% of all men, most of whom are in LMIC, smoke. In recent years, multiple measures to address initiation and continued use of tobacco products, including large increases in tobacco taxes, and packaging interventions have had significant effects on tobacco use; these preventive interventions remain the best bets for COPD control. Worldwide, 3 billion people, almost all LMIC, disproportionately women from lower socioeconomic strata, are exposed to smoke from the burning of biomass for cooking.…”
mentioning
confidence: 99%